Immunohistochemical profile of HIF-1α, VEGF-A, VEGFR2 and MMP9 proteins in tegumentary leishmaniasis Estudo da expressão imunohistoquímica das proteínas HIF-1α, VEGF-A, VEGFR2 e MMP9 em leishmaniose tegumentar americana - Carlos Alberto de Carvalho Fraga; Marcos Vinicius Macedo de Oliveira; Lucas Rodrigues Alves; Agostinho Gonçalves Viana; Adriana Alkmin de Sousa; Sílvio Fernando Guimarães Carvalho; Alfredo Maurício Batista De Paula; Ana Cristina de Carvalho Botelho; André Luiz Sena Guimarães (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Leishmaniasis is one of the most important infectious diseases worldwide. Our study can provide more knowledge about angiogenic and hypoxic events in leishmaniasis. We attempted to verify whether the HIF-1 α protein expression may be associated to VEGF-A, VEGFR2 and MMP9 in leishmanial lesions. OBJECTIVES: Besides understanding the pathway, we performed the correlation of VEGF-A, VEGFR2 and MMP9 proteins. METHODS: In this study, we gathered 54 paraffin blocks taken from skin lesions in patients from northern Minas Gerais, Brazil, with confirmed diagnosis of tegumentary leishmaniasis. Immunohistochemistry was used to evaluate the expression of the proteins. The expression of HIF-1α was categorized into two groups according to the median: HIF-1 α lower and HIF-1 α higher. RESULTS: We observed increase of VEGFR2 and MMP9 protein expressions in HIF-1 α higher group of epithelial cells. Spearman analyses in epithelial cells showed correlation between VEGF-A and MMP9, VEGFR2 and MMP9 protein expression. CONCLUSIONS: HIF-1 α higher group showed increase of VEGFR2 and MMP9 proteins. In epithelial cells, VEGF-A was correlated to MMP9 protein. Furthermore, considering leukocyte cells, VEGFR2 was negatively correlated to MMP9 protein levels. This pathway possibly prepares the cells for a higher activity in a hypoxic or an angiogenic microenvironment. Other in vitro and in vivo studies may clarify the activation mechanism and the response from the proteins HIF-1 α, VEGFR2 and MMP-9 in tegumentary leishmaniasis. FUNDAMENTOS: A leishmaniose é uma das mais importantes doenças infecciosas em todo o mundo. Em leishmaniose, tem sido sugerido que muitas características da lesão está associado a eventos de hipóxia, podendo este ter um papel fundamental na evolução da doença. OBJETIVO: O presente estudo pode fornecer dados acerca do fenômeno hipóxia e da angiogênese em leishmaniose tegumentar americana. Buscou-se verificar se a expressão da proteína HIF-1 α associa-se à expressão das proteínas VEGF-A, VEGFR2 e MMP9 em lesões de Leishmania sp. MÉTODOS: Neste estudo retrospectivo, foram utilizados 54 blocos de parafina de lesões de leishmaniose tegumentar americana de pacientes do norte de Minas Gerais, Brasil, com diagnóstico confirmado de leishmaniose tegumentar americana. A técnica de imunohistoquimica foi utilizada para avaliação da expressão das proteínas. A expressão da HIF-1α foi categorizada em dois grupos de acordo com a mediana: HIF-1 α abaixo e HIF-1 α acima da mediana. RESULTADOS: Observamos aumento das expressões das proteínas VEGFR2 e MMP9 no grupo HIF-1 α acima da mediana. A análise de Spearman demonstrou correlação entre as proteínas VEGF-A e MMP9, VEGFR2 e MMP9. CONCLUSÃO: Os dados aqui apresentados indicam uma alta expressão da proteína HIF-1 α em LTA. O grupo HIF-1α acima da mediana apresentou maior expressão das proteínas VEGFR2 e MMP9. Foi demonstrada correlação entre as proteínas VEGF-A e MMP9, VEGFR2 e MMP9. Outros estudos in vitro e in vivo devem ser realizados a fim de esclarecer o mecanismo de ativação e resposta das proteínas HIF-1 α, VEGFR2 e MMP-9 em leishmaniose tegumentar americana.